Prasugrel Versus Ticagrelor in Patients With Acute Myocardial Infarction Treated With Primary Percutaneous Coronary Intervention: Multicenter Randomized PRAGUE-18 Study - Motovska, Zuzana; Hlinomaz, Ota; Miklik, Roman; Hromadka, Milan; Varvarovsky, Ivo; Dusek, Jaroslav; Knot, Jiri; Jarkovsky, Jiri; Kala, Petr; Rokyta, Richard; Tousek, Frantisek; Kramarikova, Petra; et al. (Circulation (New York, N.Y.), 2016)
No randomized head-to-head comparison of the efficacy and safety of ticagrelor and prasugrel has been published in the 7 years since the higher efficacy of these newer P2Y inhibitors were first demonstrated relative to clopidogrel. This academic study was designed to compare the efficacy and safety of prasugrel and ticagrelor in acute myocardial infarction treated with primary or immediate percutaneous coronary intervention. A total of 1230 patients were randomly assigned across 14 sites to either prasugrel or ticagrelor, which was initiated before percutaneous coronary intervention. Nearly 4% were in cardiogenic shock, and 5.2% were on mechanical ventilation. The primary end point was defined as death, reinfarction, urgent target vessel revascularization, stroke, or serious bleeding requiring transfusion or prolonging hospitalization at 7 days (to reflect primarily the in-hospital phase). This analysis presents data from the first 30 days (key secondary end point). The total follow-up will be 1 year for all patients and will be completed in 2017. The study was prematurely terminated for futility. The occurrence of the primary end point did not differ between groups receiving prasugrel and ticagrelor (4.0% and 4.1%, respectively; odds ratio, 0.98; 95% confidence interval, 0.55-1.73; P=0.939). No significant difference was found in any of the components of the primary end point. The occurrence of key secondary end point within 30 days, composed of cardiovascular death, nonfatal myocardial infarction, or stroke, did not show any significant difference between prasugrel and ticagrelor (2.7% and 2.5%, respectively; odds ratio, 1.06; 95% confidence interval, 0.53-2.15; P=0.864). This head-to-head comparison of prasugrel and ticagrelor does not support the hypothesis that one is more effective or safer than the other in preventing ischemic and bleeding events in the acute phase of myocardial infarction treated with a primary percutaneous coronary intervention strategy. The observed rates of major outcomes were similar but with broad confidence intervals around the estimates. These interesting observations need to be confirmed in a larger trial. URL: http://www.ClinicalTrials.gov. Unique identifier: NCT02808767.